Creating a Culture of Safety Around Bar-Code Medication Administration: An Evidence-Based Evaluation Framework. (January 2016) - Kelly, Kandace; Harrington, Linda; Matos, Pat; Turner, Barbara; Johnson, Constance
Abstract : Bar-code medication administration (BCMA) effectiveness is contingent upon compliance with best-practice protocols. We developed a 4-phased BCMA evaluation program to evaluate the degree of integration of current evidence into BCMA policies, procedures, and practices; identify barriers to best-practice BCMA use; and modify BCMA practice in concert with changes to the practice environment. This program provides an infrastructure for frontline nurses to partner with hospital leaders to continually evaluate and improve BCMA using a systematic process.